A comparison of the system engineering standard and INCOSE Complexity Primer. (2nd May 2021) - Kovacic, Samuel; Sousa-Poza, Andres
Complexity is frequently used to describe the environment in which systems engineering must work. Relevant publications establish a relationship between complexity and understanding, however, it is questionable whether system engineering methodologies are well suited to deal with complexity and potential lack of understanding. This paper provides an analysis between the System Engineering standard and the INCOSE Complexity Primer to assess the standard and the nature of complexity in systems. The analysis conducted shows that present descriptions of how complexity create a problem space that is distinctly different to the problem space that can be addressed by present practices. Furthermore, it was found that System Engineering methodology described within the standard will encounter significant challenges in dealing with the attributes of complexity documented in the INCOSE Complexity Primer. Additionally, a crosswalk is conducted between complex systems as describe by the primer and system of systems (SoS) to illicit similarities or differences.